miR-654-5p Contributes to the Activation and Proliferation of Hepatic Stellate Cells by Targeting RXRα - Ma, Heming; Wang, Xiaomei; Liu, Xu; Wang, Chang; Gao, Xiuzhu; Niu, Junqi (Frontiers in Cell and Developmental Biology, 2022)
Liver fibrosis (LF) is a major disease that threatens human health. Hepatic stellate cells (HSCs) contribute directly to LF via extracellular matrix (ECM) secretion. Moreover, RXRα is an important nuclear receptor that plays a key regulatory role in HSC activation. Meanwhile, microRNAs (miRNAs) have been identified as significant regulators of LF development. In particular, miR-654-5p is involved in cellular migration and proliferation, and via bioinformatics analysis, has been identified as a potential factor that targets RXRα in humans and in mice. However, the precise relationship between miR-654-5p and RXRα in the context of LF, remains unknown and is the primary focus of the current study. To establish in vitro activated cell model human primary HSCs were cultured in vitro and LX-2 cells were stimulated with recombinant human TGF-β1. mRNA and protein levels of RXRα, miR-654-5p and fibrogenic genes were compared in quiescent and activated HSCs. Moreover, after transfected with miR-654-5p mimics, the expression changes of above related genes in LX-2 cells were estimated. Meanwhile, cell proliferation and apoptosis were detected in miR-654-5p overexpressed LX-2 cells. Simultaneously, the targeted binding between miR-654-5p and RXRα was verified in LX-2 cells. Carbon tetrachloride (CCl4)-induced mouse model with liver fibrosis was use to research the role of the miR-654-5p in vitro. Our results show that miR-654-5p expression levels increased in activated human HSCs and TGFβ-treated LX-2 cells. Moreover, miR-654-5p mimics markedly promoted LX-2 cell proliferation while inhibiting their apoptosis. Accordingly, the expression levels of RXRα are decreased in activated HSCs and LX-2 cells. Additionally, dual-luciferase reporter assay results reveal direct targeting of RXRα by miR-654-5p. Similarly, in vivo miR-654-5p overexpression aggravates LF in mice that are intraperitoneally injected with CCl4. Taken together, our findings elucidated a novel molecular mechanism with potential use for treatment of LF.